Les éclats du développement - Juan Pedro Blois; Mariana Heredia (Revue d’Histoire des Sciences Humaines)
Modern knowledge advances by subdividing specialized knowledge. But the boundaries between disciplines and professions are not inscribed in nature. The relations between economics and sociology are interesting because they have been marked by cycles of proximity and distancing. In Argentina, the enthronement of « development » in the 1950s as a public policy objective and the focus of academic agendas facilitated convergence. Both state and international institutions took Latin America as a singular object that demanded the assistance of both specialists. In contrast, the dictatorial government of 1976 intervened in the university and public administration, forced many researchers into exile, and encouraged antagonism between economists and sociologists. Based on a large corpus, this paper reconstructs the history of this link and shows how local crises and external influences encouraged cooperation, opposition, and indifference between these specialists.